Kinematic analysis of top spin forehand with celluloid and plastic ball - Malagoli Lanzoni, I.; Farina, M.; Nardella, I.; Fantozzi, S. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The top spin forehand (TSF) was always considered the most important and aggressive shot in Table Tennis. In 2014, the International Table Tennis Federation decided to introduce a new kind of ball, maintaining the same diameter (40 mm) but changing the material used from celluloid to plastic. The purpose of this study is to compare the kinematic of TSF, comparing the techniques used with the celluloid ball (CB) and the new plastic ball (PB). Ten male elite athletes were involved in the study (age 22.7 ± 7.4 years, height 177.3 ± 4.4 cm, mass 74.2 ± 10.7 kg). After a warm-up, the athletes were asked to play crosscourt TSF with the same racquet. A Ball machine (Joola Compact) served balls (speed level 7 and freq. level 1) in the forehand corner. The participants performed ten cross TSF with the CB and ten with PB into a target at the opposite side of the table (40x65 cm). For the kinematic analysis a stereo-photogrammetric system was used (Smart-D, BTS, 10 cameras, 500 Hz) and a total of 44 markers were attached on the athletes` skin. Further markers were attached on the table (four) and on the racquet (five). Results showed no differences in kinematics variables of upper and lower limbs between TSF performed with CB and PB. The kinematic variables are angles between (expressed in degrees): shoulders-table (max, impact, and min), shoulder-racquet-table (max and impact), pelvis-table (max, impact, and min), elbow flexion/extension (max, impact, and min), knee flexion/extension (max, impact, and min), and feet-table (mean value). This study shows that the type of ball has no substantial influence, this suggests that these athletes are able to adapt their technique to varying playing materials.